From policy to school: embedding career orientation as a cross-curricular area in Bosnia and Herzegovina - Isanović Hadžiomerović, Amina (Frontiers in Education, 2025)
This article explores the integration of Career Orientation as a cross-curricular area within the Core Curriculum in Bosnia and Herzegovina, drawing on a neo-Deweyan theoretical framework which approaches curriculum as a multilayered structure composed of epistemological, pedagogical, anthropological and ecological dimensions. The paper analyzes how key concepts of career orientation are framed in the curriculum and what learning outcomes and pedagogical guidelines are proposed. The results show gap between declarative aspirations presented in the curriculum documents and the necessary prerequisites in practice for implementation of Career Orientation as a cross-curricular area. Analysis shows that the curriculum reflects a declarative shift toward a new learning paradigm in career guidance—one that is dedicated to developing career management skills—rather than the traditional model focused on testing, matching and decision-making. Career Orientation is described as an active, reflective and student-centered process, aligned with broader goals of lifelong learning and personal agency. Additionally, referring to the collaborative and interdisciplinary nature of cross-curricularity, the paper argues that the implementation of Career Orientation depends not only on epistemological and pedagogical dimensions, but also on the ecological, e.g., schools’ capacity to adopt collaborative, participatory and learner-centered teaching practices. Stemming from this part of the research several challenges to implementation of Career Orientation as cross-curricular area were identified, including insufficient teacher support, limited opportunities for teacher collaboration and a lack of adequate educational resources. To ensure further development and sustainability of Career Orientation as a cross-curricular area, the results indicate the need for enhancing the conditions concerning the overall curriculum implementation focusing primarily on developing the professional culture that fosters collaboration, shared responsibility and focuses on students as active learners, as these are at the heart of cross-curricular approaches.